Partially collapsed cristobalite structure in the non molecular phase V in CO2 - Santoro, Mario; Gorelli, Federico A; Bini, Roberto; Haines, Julien; Cambon, Olivier; Levelut, Claire; Montoya, Javier A; Scandolo, Sandro (Proceedings of the National Academy of Sciences - PNAS, 2012)
Non molecular CO2 has been an important subject of study in high pressure physics and chemistry for the past decade opening up a unique area of carbon chemistry. The phase diagram of CO2 includes several non molecular phases above 30 GPa. Among these, the first discovered was CO2-V which appeared silica-like. Theoretical studies suggested that the structure of CO2-V is related to that of β-cristobalite with tetrahedral carbon coordination similar to silicon in SiO2, but reported experimental structural studies have been controversial. We have investigated CO2-V obtained from molecular CO2 at 40–50 GPa and T > 1500 K using synchrotron X-ray diffraction, optical spectroscopy, and computer simulations. The structure refined by the Rietveld method is a partially collapsed variant of SiO2 β-cristobalite, space group Formula , in which the CO4 tetrahedra are tilted by 38.4° about the c-axis. The existence of CO4 tetrahedra (average O-C-O angle of 109.5°) is thus confirmed. The results add to the knowledge of carbon chemistry with mineral phases similar to SiO2 and potential implications for Earth and planetary interiors.